Living Donor Nephrectomy: Is It as Safe as It Can Be? Analysis of Living Donor Deaths in the United States. Issue 4 (December 2019) - Keith, Douglas Scott; Brown, Joe; Andreoni, Kenneth
Abstract : Introduction: The reported 90-day rate of death from living donor nephrectomy is 3 in 10, 000 donations. Although this risk is low, the important question is how many deaths are preventable? Methods: To study this question, all living donor nephrectomy cases, 139, 186 procedures, recorded in the Scientific Registry of Transplant Recipients database since its inception in 1987 were analyzed to determine the death rate and the number of deaths that were potentially preventable. Preventable deaths were defined as any death in the first 7 days except due to clearly unrelated events or death from hemorrhage, pulmonary embolism, infection, cardiovascular cause, or suicide in the first 90 days. Results: The numbers of deaths at 7, 30, 90, and 365 days after donation were 16, 26, 38, and 86, which translated into 1.15, 1.87, 2.73, and 6.18 deaths per 10, 000 donations, respectively. From 2000 onward, when coding was available for cause of death, 19 of the 30 deaths were deemed potentially preventable. The nonrisk-adjusted rate of death with laparoscopic donation was higher than open nephrectomy, but this difference did not reach statistical significance. Conversion from laparoscopic to open nephrectomy occurs in approximately 1 in 100 surgeries, and this rate has remained fairly steady since 2005. Conclusions: This analysis suggests that up to two thirds of deaths are potentially preventable. The transplant community should consider additional safety strategies such as simulation training of rare complications to lower donor risk.